An ultrastructural and histochemical study of the flexor tibialis muscle fiber types in male and female stick insects (Eurycantha calcarata, L). Issue 8 (14th July 2015) - Pilehvarian, Ali Asghar
Abstract In this study the ultrastructural and histochemical characteristics of the flexor tibialis muscle fibers of the specialized metathoracic legs in the male and those of homologous and unspecialized ones in the female stick insects, Eurycantha calcarata, L, were examined. For the ultrastructural analysis, the muscle was divided longitudinally and vertically to produce a total of 12 sample parts e.g., anterior‐dorsal‐distal (ADD), posterior‐ventral‐medial (PVM) and so on. Light and electron microscopes were used to observe the muscle tissue. The methods for myosin adenosine triphosphatase (mATPase) and nicotine adenine dinucleotide‐ tetrazolium (NADH‐TR) staining were modified from the methods of (Stokes et al., '79; Anttila et al., 2009; Anttila and Manttari, 2009). Sections with thickness of 22 μm, were cut from the anterior and the posterior surfaces of the muscle, using a cryostat. The histochemical and ultrastructural results showed that the muscles of both the male and the female were mixtures of physiological fiber types, with predominantly fast fibers. The muscles were composed of fibers with different staining properties for both mATPase and NADH‐TR activities. The population of fibers within the muscles was heterogeneous. The differences between the population of the male and that of the female were significant. The means of most criteria e.g., mitochondrial amount and sarcoplasmic reticulum area predicted that the muscle of the male contained more fast fibers than the female. The histochemical examination also showed that the muscle of the male contained more fibers stained darkly for mATPase and lightly for NADH‐TR. J. Exp. Zool. 323A: 527–539, 2015. © 2015 Wiley Periodicals, Inc.